Effect of the deflector plate on hydraulic performance and optimization of impact sprinkler nozzle - LI Haoyu; LI Tao; DI Yahe (Guan'gai paishui xuebao)
【Objective】Irrigation uniformity is a critical parameter in irrigation design. This study investigates the effect of deflector plate on optimization and hydraulic performance of impact sprinkler nozzles.【Method】A 3D model of an impact sprinkler nozzle was developed using SolidWorks, and a guide vane nozzle was designed for the 20PY2H sprinkler. The nozzle was fabricated using 3D printing to enable rapid prototyping and easy modification. Field experiments were conducted using an orthogonal experimental design. Two structural parameters, the number of guide vanes and the vane width, were selected as the influencing factors. Hydraulic performance indicators such as throw range, flow rate, point irrigation intensity, and irrigation uniformity were measured during the experiment. A multi-index evaluation method was used to determine the optimal structural configuration.【Result】Increasing the number of guide vanes reduced the average throw range, although the performance of N1W3.5 and N2W2.5 configurations were comparable to the original nozzle. Increasing vane width increased hydraulic resistance and energy loss. The average sprinkler intensity of single nozzle ranged from 2.87 mm/h to 4.53 mm/h. When the number of vane are the same, sprinkler intensity initially increased and then decreased as vane width decreased, indicating a nonlinear relationship between them. Radial water distribution patterns were categorized as ‘near single-peak’ ‘far single-peak’, and ‘gentle’. Compared to the standard nozzle, the N3W2.5 configuration enhanced water distribution stabilization, irrigation uniformity, and spraying intensity between 12 mm/h and 17 mm/h.【Conclusion】Under the tested working pressure, the optimal guide vane configuration was three vanes with a width of 2.5 mm, which achieved a throw range of 17.50 m, sprinkler intensity of 4.42 mm/h, and a uniformity coefficient of 91.20%. Structural optimization of the guide vane nozzle, supported by orthogonal testing and comprehensive evaluation, significantly improved the uniformity and efficiency of impact sprinkler nozzles. These findings offer valuable insights for improving future sprinkler nozzle designs.